1979
DOI: 10.1104/pp.63.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Light-harvesting Pigment-Protein Complex of Wild Type and a Chlorophyll-b-less Mutant of Barley

Abstract: We have compared chloroplast lamellae isolated from a chlorophyll-bless mutant and wild type barley (Hordeum vulgare). The results demonstrate that: (a) one of the two major polypeptides comprising the lightharvesting complex (LHC) is present in the chlorophyll-b-less mutant; (b) higher cation concentrations are required to maintain grana stacks in the mutant; and (c) cation effects on excitation energy distribution are present in the chlorophyll-b-less mutant but are reduced in amount and are 'dependent on hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 17 publications
(28 reference statements)
6
33
1
Order By: Relevance
“…The position in the gel after electrophoresis, absorption spectrum, and pigment content of the algal PSII complex are all properties similar to PSII from higher plants; but, like PSI, its relative proportion seems to be lower (7% compared to 15% for spinach, Table I (9), probably because these pigment-proteins without Chl b are extremely labile and more susceptible to both protease and detergent action (12). The procedure used to isolate a Chl a antenna complex from the Chlorina-f2 barley mutant was the same as that applied here to N. salina, and the gel pattern for the fastest running green bands (LHCII and FP) were similar ( Table I).…”
Section: Resultsmentioning
confidence: 99%
“…The position in the gel after electrophoresis, absorption spectrum, and pigment content of the algal PSII complex are all properties similar to PSII from higher plants; but, like PSI, its relative proportion seems to be lower (7% compared to 15% for spinach, Table I (9), probably because these pigment-proteins without Chl b are extremely labile and more susceptible to both protease and detergent action (12). The procedure used to isolate a Chl a antenna complex from the Chlorina-f2 barley mutant was the same as that applied here to N. salina, and the gel pattern for the fastest running green bands (LHCII and FP) were similar ( Table I).…”
Section: Resultsmentioning
confidence: 99%
“…This is expected if there is a nonuniform loss of CPI in the chloroplasts. If the reduction in chlorophyll were due to loss of the light harvesting complex, as in the well-documented barley chlorina f2 mutant (Burke et al, 1979), a shift in the 740-nm band to the 720-to 725-nm region would be expected. The decrease in the chlorophyll alb ratio as well as the reduction, rather than a shift of the 740-nm fluorescence band, argues for an effect on the PSllCPl thylakoid complex in the yellow sectors.…”
Section: Discussionmentioning
confidence: 99%
“…. (i) Simpson [46] showed that the EFs particles of a chl b-less mutant barley which lacks one of the LHCP polypeptides [47] were only 12% smaller than those of wild type barley. Since there was a 50% decrease in the number of PFs particles in mutant barley, he concludes that some LHCP is located in PFs particles which are closely associated with EFs particles.…”
Section: Correlations Of Structure and Functionmentioning
confidence: 99%